2022
DOI: 10.1016/j.metabol.2022.155156
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization study of obesity and type 2 diabetes in hospitalized COVID-19 patients

Abstract: Background: Both obesity and type 2 diabetes (T2D) are reported to be highly enriched in hospitalized COVID-19 patients. Due to the close correlation between obesity and T2D, it is important to examine whether obesity and T2D are independently related to COVID-19 hospitalization. Objective: To examine the causal effect of obesity and T2D in hospitalized COVID-19 patients using Mendelian randomization (MR).Research design and methods: This two-sample MR analysis applied genetic markers of obesity identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
2
21
1
Order By: Relevance
“…In agreement with this, Byun et al utilized the summarized data from the UK Biobank observed robust positive genetic correlations between diabetes and COVID-19 severity ( r g = 0.254) or hospitalization ( r g = 0.309) [ 32 ]. We found that genetically predicted T2D did not increase the risk of COVID-19 severity, in keeping with earlier MR studies employing data from the previous data freeze (COVID-19 HGI, release 3 and 4, 2020) with smaller sample size for hospitalized as well as severe COVID-19 cases [ 33 , 34 ]. Our current work also improves on previous MR investigations, as multiple complementary MR techniques and sensitivity analysis (MR-PRESSO and manually pruning pleiotropic variants) were performed to appraise the robustness of causal inference.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with this, Byun et al utilized the summarized data from the UK Biobank observed robust positive genetic correlations between diabetes and COVID-19 severity ( r g = 0.254) or hospitalization ( r g = 0.309) [ 32 ]. We found that genetically predicted T2D did not increase the risk of COVID-19 severity, in keeping with earlier MR studies employing data from the previous data freeze (COVID-19 HGI, release 3 and 4, 2020) with smaller sample size for hospitalized as well as severe COVID-19 cases [ 33 , 34 ]. Our current work also improves on previous MR investigations, as multiple complementary MR techniques and sensitivity analysis (MR-PRESSO and manually pruning pleiotropic variants) were performed to appraise the robustness of causal inference.…”
Section: Discussionsupporting
confidence: 91%
“…Although previous MR analyses did not detect causal associations between T2D and COVID‐19, 1 , 24 , 28 , 29 , 30 our study revealed robust causal associations between T2D and severe outcomes of COVID‐19, namely, hospitalized COVID‐19 and critical COVID‐19. A possible explanation for newly discovered significant associations is an increase in the study power achieved by employing larger data sets for both COVID‐19 and T2D.…”
Section: Discussioncontrasting
confidence: 85%
“… 1 , 2 , 3 Since T2D has been suggested as an additional risk factor for COVID‐19, several previous studies were conducted to investigate the possible causality of this relationship. 1 , 24 , 28 , 29 , 30 However, no causal associations between T2D and COVID‐19 have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to also emphasize the strong relationship between the two pandemics, the obesity and the COVID-19 pandemic, that coexist and synergize, since it has repeatedly been shown after we first reported that, in a way, one exacerbates the other [38] . Several studies have shown that patients with COVID-19 and obesity have increased risk for severe disease, hospitalization, incubation, and death [38] , [39] , [40] , [41] , [42] , [43] . This is not surprising since it has been described that obesity causes increased work of breathing by inducing the airway resistance and decreases expiratory reserve volume, functional capacity, and pulmonary compliance.…”
Section: Discussionmentioning
confidence: 99%